Characterization of white matter hyperintensities in Down syndrome - Morcillo‐Nieto, Alejandra O.; Zsadanyi, Sara E.; Arriola‐Infante, Jose E.; Carmona‐Iragui, Maria; Montal, Victor; Pegueroles, Jordi; Aranha, Mateus Rozalem; Vaqué‐Alcázar, Lídia; Padilla, Concepción; Benejam, Bessy; Videla, Laura; Barroeta, Isabel; et al. (Alzheimer's & dementia, 2024)
INTRODUCTION In Down syndrome (DS), white matter hyperintensities (WMHs) are highly prevalent, yet their topography and association with sociodemographic data and Alzheimer's disease (AD) biomarkers remain largely unexplored. METHODS In 261 DS adults and 131 euploid controls, fluid‐attenuated inversion recovery magnetic resonance imaging scans were segmented and WMHs were extracted in concentric white matter layers and lobar regions. We tested associations with AD clinical stages, sociodemographic data, cerebrospinal fluid (CSF) AD biomarkers, and gray matter (GM) volume. RESULTS In DS, total WMHs arose at age 43 and showed stronger associations with age than in controls. WMH volume increased along the AD continuum, particularly in periventricular regions, and frontal, parietal, and occipital lobes. Associations were found with CSF biomarkers and temporo‐parietal GM volumes. DISCUSSION WMHs increase 10 years before AD symptom onset in DS and are closely linked with AD biomarkers and neurodegeneration. This suggests a direct connection to AD pathophysiology, independent of vascular risks. Highlights White matter hyperintensities (WMHs) increased 10 years before Alzheimer's disease symptom onset in Down syndrome (DS). WMHs were strongly associated in DS with the neurofilament light chain biomarker. WMHs were more associated in DS with gray matter volume in parieto‐temporal areas.